FREIGHT MANAGEMENT IN THE CONDITIONS OF RISKS OF THE COMPETITIVE ENVIRONMENT - Bekh, P. V.; Nesterenko, H. I.; Strelko, O. H.; Muzykin, M. I. (Systems and Technologies, 2021)
The main problem facing Ukrzaliznytsia is to increase profitability and competitiveness by improving the quality of service, improving tariff policy, technology and organization of freight.This problem is a set of tasks related to the organization of freight.The nature and dynamics of these processes is largely determined by the structure of the market itself, within which there are two main interacting entities: the transport system and consumers of transport products – shippers and consignees. Their strategy of behavior achieves the main goal – to win the most profitable, dominant position in the transport market.Therefore, to form an equilibrium state in the market of transport services it is necessary to achieve a reasonable compromise between the subjects of the competitive environment, which allows to obtain an integrated economic effect for all market participants.Freight traffic is the main source of income for the railways. Their technology and organization fully determine all the economic performance of the railways. Therefore, first of all it is necessary to consider the state of this most important area of functioning of railway transport.The transition to a market economy has dramatically changed the possibilities of freight planning, which has become more difficult to implement, but remained no less necessary.There has long been a problem of computer operational adjustment of formation plans, the main purpose of which should be to accelerate the promotion of car traffic, as well as the allocation of destinations for increased transit.And only in the conditions of adjustment of plans of formation on the basis of the periodic and continuous information in close interaction with operational planning and the dispatching management of all levels it is possible to receive the most effective system of management of processes of freight transportations.Uncertainty of the time of arrival of goods reduces the competitiveness of rail transport, sharply complicates the interaction with other modes of transport, such as delivery of all goods for shipment by this vessel, which has become especially necessary in the emerging transport corridors.Ukraine has relatively well-developed highways, not to mention European countries, which are not so far away. Therefore, users of transport products are increasingly making their choice not in favor of rail transport.While the railways have not lost demand for their services and are making a profit, not all cargo is transported by road and water – it is necessary to immediately take measures to increase the competitiveness of Ukrainian rail transport.